2003
DOI: 10.1016/s0378-1097(02)01189-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomics-based design of defined growth media for the plant pathogenXylella fastidiosa

Abstract: Based on the genetic analysis of the phytopathogen Xylella fastidiosa genome, five media with defined composition were developed and the growth abilities of this fastidious prokaryote were evaluated in liquid media and on solid plates. All media had a common salt composition and included the same amounts of glucose and vitamins but differed in their amino acid content. XDM 1 medium contained amino acids threonine, serine, glycine, alanine, aspartic acid and glutamic acid, for which complete degradation pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 27 publications
(38 reference statements)
1
56
0
5
Order By: Relevance
“…Isolation of bioactives from environmental bacteria, however, faces the limitation that many strains are recalcitrant to culturing (1,33,48,51), and this might be particularly true for obligate or facultative symbionts. To access the uncultured majority of the microbial world (43), functional metagenomic approaches that allow for the expression of environmental DNA from uncultured organisms in surrogate hosts have been developed (6,22,32,35,36,46).…”
mentioning
confidence: 99%
“…Isolation of bioactives from environmental bacteria, however, faces the limitation that many strains are recalcitrant to culturing (1,33,48,51), and this might be particularly true for obligate or facultative symbionts. To access the uncultured majority of the microbial world (43), functional metagenomic approaches that allow for the expression of environmental DNA from uncultured organisms in surrogate hosts have been developed (6,22,32,35,36,46).…”
mentioning
confidence: 99%
“…Owing to the increasing availability of sequenced rust genomes, a knowledge of genes or gene families encoding enzymes that are essential for important biochemical pathways could soon become a reality (Duplessis et al 2011). Such findings may be vital for a more accurate delineation of the nutritional requirements of rusts and thus bring about a marked improvement of current growth media, such an improvement has already occurred for other groups of obligate plant parasites (Lemos et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…An early example of genome-inspired medium design was the development of a defined medium for Xylella fastidiosa, a slow-growing plant pathogen inhabiting the xylem of citrus plants (Lemos et al 2003;Almeida et al 2004;Janse & Obradovic 2010). Even though the organism had been isolated with empirical methods before (Wells et al 1987), and its genome was sequenced in 2000 (Setubal et al 2000), Lemos et al (2003) revealed that a relatively simple medium composition supported growth.…”
Section: Host Associatedmentioning
confidence: 99%
“…Even though the organism had been isolated with empirical methods before (Wells et al 1987), and its genome was sequenced in 2000 (Setubal et al 2000), Lemos et al (2003) revealed that a relatively simple medium composition supported growth. They prepared five minimal media that differed in amino acid composition and concentration based on the presence or absence of genes for amino acid biosynthetic pathways in the X. fastidiosa genome.…”
Section: Host Associatedmentioning
confidence: 99%
See 1 more Smart Citation